What is mental fatigue in elite sport? Perceptions from athletes and staff. Issue 10 (26th November 2019) - Russell, Suzanna; Jenkins, David; Rynne, Steven; Halson, Shona L.; Kelly, Vincent
Abstract: Mental fatigue is a psychobiological state caused by prolonged periods of demanding cognitive activity shown to negatively influence physical performance. Variation exists across the literature regarding the manifestations and impact of mental fatigue; with little knowledge of the domain-specific manifestations in elite sport. The difficulties in defining mental fatigue may explain why it is not consistently assessed by coaching or support staff. The aim of this study was therefore to investigate athlete and staff understandings of mental fatigue in elite sport. Nine focus group discussions were conducted involving a total of 32 athletes ( n = 17) and staff ( n = 15) from elite sporting organisations. Athletes and staff believe mental fatigue negatively impacts sporting performance. Analysis revealed perceived associations between mental fatigue and changes in behaviour including, disengagement, decreased motivation and enthusiasm, increased displays of emotion and withdrawal. Changes in concentration, decreased discipline and attention to detail also emerged as descriptors of mental fatigue. Media engagements, study and work commitments were reported to induce mental fatigue. Repetitive tasks, over-analysis, thinking about the sport in question and environmental instability were further reported perceived causes. Experience and personality emerged as factors contributing to individual susceptibility. Mental fatigue is perceived to not only develop acutely but also build in a cumulative manner in the elite sporting environment. The present findings inform the design of future studies examining MF in elite athletes; they also hold the potential to improve how best to monitor and manage the condition in applied practice.